2016
DOI: 10.1017/s1355617716000230
|View full text |Cite
|
Sign up to set email alerts
|

Serum Brain-Derived Neurotrophic Factor Mediates the Relationship between Abdominal Adiposity and Executive Function in Middle Age

Abstract: The relationship between higher WHR and verbal fluency was fully statistically mediated by circulating BDNF levels. The BDNF pathway is thus a useful probable mechanism through which executive function decline occurs in individuals with high abdominal adiposity. BDNF enhancing interventions (physical exercise and dietary restriction) could thus be used to improve executive function in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…Thus, reduction of this parameter would be extremely relevant, and these trends toward change were observed for the HIIT group and not MICT. IL-6 did not change from pre-to post-intervention in either group, which might be expected given that no significant differences were found in visceral fat, a main resource of inflammation in www.nature.com/scientificreports/ obesity [1][2][3] . In addition, Batacan et al 28 argue the effect of HIIT on cytokines, such as IL-6, is still not clear, especially because the number of studies is small and there is high variability among protocols (shorter and longer).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, reduction of this parameter would be extremely relevant, and these trends toward change were observed for the HIIT group and not MICT. IL-6 did not change from pre-to post-intervention in either group, which might be expected given that no significant differences were found in visceral fat, a main resource of inflammation in www.nature.com/scientificreports/ obesity [1][2][3] . In addition, Batacan et al 28 argue the effect of HIIT on cytokines, such as IL-6, is still not clear, especially because the number of studies is small and there is high variability among protocols (shorter and longer).…”
Section: Discussionmentioning
confidence: 73%
“…There is evidence of an association between augmented abdominal adiposity and lower cognitive function, and it seems that one link between these two parameters is through immunometabolic alterations provoked by pro-inflammatory cytokines, such as interleukin-6 (IL-6), released from adipose tissue 1 3 . Aspects of cognition, such as executive function, which includes working memory, inhibitory control and cognitive flexibility 2 , 4 , 5 , can be affected by the size of visceral fat 1 and metabolic dysfunction 3 , 6 , which are very common conditions in subjects with obesity. In this context, both abdominal fat and cognitive impairments seem to be associated with lower concentrations of brain-derived neurotrophic factor (BDNF) 2 , 7 , an important pleiotropic protein directly related to neuron health and brain function 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, both cadmium and lead exposures have been shown to reduce the levels of BDNF [8,92.93], an obesity related gene that regulates energy balance [94]. Meanwhile, lower methylation of BDNF promoter in the salivary DNA of obese adolescents has also been reported [36] while increased adiposity is related to decreased levels of circulating BDNF [95]. Likewise, prenatal lead exposure results in decreased spontaneous motor activity, altered dopamine levels and obesity in adult male mice [69].…”
Section: Potential Mechanisms By Which Cadmium and Lead May Alter Obesimentioning
confidence: 99%
“…It is noteworthy that adiponectin is an adipocyte-derived hormone and at increased levels may be important indicative of the development of obesity and cardiovascular diseases (34). In this context, it was observed that increased adiposity was also associated with low circulating levels of BDNF (35). These considerations raised the possibility that interventions such as physical exercise and food restriction can modulate WHR and also improve executive function.…”
Section: Discussionmentioning
confidence: 99%